Genome-wide oxidative bisulfite sequencing identifies sex-specific methylation differences in the human placenta. Issue 3 (4th March 2018) - Gong, Sungsam; Johnson, Michelle D; Dopierala, Justyna; Gaccioli, Francesca; Sovio, Ulla; Constância, Miguel; Smith, Gordon CS; Charnock-Jones, D Stephen
ABSTRACT: DNA methylation is an important regulator of gene function. Fetal sex is associated with the risk of several specific pregnancy complications related to placental function. However, the association between fetal sex and placental DNA methylation remains poorly understood. We carried out whole-genome oxidative bisulfite sequencing in the placentas of two healthy female and two healthy male pregnancies generating an average genome depth of coverage of 25x. Most highly ranked differentially methylated regions (DMRs) were located on the X chromosome but we identified a 225 kb sex-specific DMR in the body of the CUB and Sushi Multiple Domains 1 ( CSMD1 ) gene on chromosome 8. The sex-specific differential methylation pattern observed in this region was validated in additional placentas using in-solution target capture. In a new RNA-seq data set from 64 female and 67 male placentas, CSMD1 mRNA was 1.8-fold higher in male than in female placentas ( P value = 8.5 × 10 −7, Mann-Whitney test). Exon-level quantification of CSMD1 mRNA from these 131 placentas suggested a likely placenta-specific CSMD1 isoform not detected in the 21 somatic tissues analyzed. We show that the gene body of an autosomal gene, CSMD1, is differentially methylated in a sex- and placental-specific manner, displaying sex-specific differences in placental transcript abundance.